Development of a servo-based broaching machine using virtual prototyping technology - Park, Hong Seok (Strojniški vestnik, 2017)
Predicting machine tool performance at the design stage is one way to resolve the time issue and achieve cost savings. The objective of this paper was to develop a new non-hydraulic broaching machine using a servo motor, ball screw, and roll element linear guide using virtual prototyping technology. First, we developed a multi-body simulation model (MBS) of a servo-based broaching machine to investigate its dynamic behaviour. Then, an adaptive sliding mode proportional-integral-derivative (PID)-based controller (ASMPID) was proposed to conduct the broaching process. We then performed a co-simulation between the mechanical structure and virtual controller to investigate the ram body trajectory and identify the optimal control parameters. Finally, we manufactured a prototype machine to evaluate the simulation results and determine the benefits of the new system. Our results indicated that the proposed model, which includes a mechanical structure and intelligent controller, effectively improved broaching machine design. Therefore, this work is expected to improve the prototyping efficiency of new broaching machines.
Keywords: adaptivno krmiljenje z drsnim režimom; kroglična vretena; servomotorji; simulacija več teles; stroj za posnemanje; tehnologija virtualne izdelave prototipov